Reasons for Choosing Medicine and Career Suitability among Medical Students - Khairani, O; Mohamed, NA; Ismail, Z; Shalinawati, R; Chamhuri, NH; Nur Syahrina Rahim (Univ Kebangsaan Malaysia, Fac Medicine, 2024)
Indexed by WOS